Detection and proportion of very early dental caries in independent living older adults. Issue 9 (28th September 2015) - Holtzman, Jennifer S.; Kohanchi, Daniel; Biren‐Fetz, John; Fontana, Margherita; Ramchandani, Manisha; Osann, Kathryn; Hallajian, Lucy; Mansour, Stephanie; Nabelsi, Tasneem; Chung, Na Eun; Wilder‐Smith, Petra
<x xml:space="preserve">Abstract</x> Background and Objectives Dental caries is an important healthcare challenge in adults over 65 years of age. Integration of oral health screening into non‐dental primary care practice may improve access to preventive dental care for vulnerable populations such as the elderly. Such integration would require easy, fast, and accurate early caries detection tools. Primary goal of this study was to evaluate the diagnostic performance of optical coherence tomography (OCT) imaging for detecting very early caries in the elderly living in community‐based settings. The International Caries Detection and Assessment System (ICDAS) served as gold standard. Secondary goal of this study was to provide baseline prevalence data of very early caries lesions in independent living adults aged 65+ years. Materials and Methods Seventy‐two subjects were recruited from three sites in Southern California: a retirement community, a senior health fair, and a convalescent hospital. Clinical examination was performed using the ICDAS visual criteria and this was followed by OCT imaging. The two‐dimensional OCT images (B‐scan) were analyzed with simple software. Locations with a log of back‐scattered light intensity (BSLI) below 2.9 were scored as sound, and areas equaling or exceeding 2.9 BSLI were considered carious. Diagnostic performance of OCT imaging was compared with ICDAS score. Results OCT‐based diagnosis demonstrated very good sensitivity (95.1%) and good specificity (85.8%). 54.7% of dentate subjects had at least one tooth with very early coronal caries. Conclusions Early coronal decay is prevalent in the unrestored pits and fissures of coronal surfaces of teeth in independent living adults aged 65+ years. Though OCT imaging coupled with a simple diagnostic algorithm can accurately detect areas of very early caries in community‐based settings, existing devices are expensive and not well‐suited for use by non‐dental health care providers. Simple, inexpensive, fast, and accurate tools for early caries detection by field health care providers working in non‐traditional settings are urgently needed to support inter‐professional dental health management. Lasers Surg. Med. 47:683–688, 2015. © 2015 Wiley Periodicals, Inc.